KEPUTUSAN PEMBELIAN SMARTPHONE XIAOMI: Studi Kasus Pada Kelurahan Cipedak Jakarta Selatan - Veriandriano, - (2019)
This research is a quantitative research that aims to determine the effect of price, advertising, and product attributes on brand switching. The population in this study were Simpati users in kelurahan cipedak Jakarta selatan. The sample size was taken as many as 60 respondents, with a non probability sampling method with a purposive sampling method. Data collection is done through the distribution of questionnaires. The analysis technique used is the method of PLS (Partial Least Square) analysis with SmartPLS3.0 software. The results of this study indicate that (1) Brand image a significant influence on purchasing decisions.(2) Quality product has a significant to purchesing dicisions (3) Price has a significant influence on purchesing dicisions.